1999
DOI: 10.1038/sj.onc.1203055
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of activated neu/erbB2 initiates immortalization and malignant transformation of immature Schwann cells in vitro

Abstract: The neu/erbB2 protooncogene is overexpressed in numerous human cancers and is mutationally activated in N-ethyl-N-nitrosourea (ENU)-induced rodent tumors of the Schwann cell lineage. We investigated whether expression of activated neu in Schwann cells is su cient to initiate their immortalization and transformation. Clones of embryonic dorsal root ganglia cells infected with a retrovirus bearing activated neu (NID cells) were selected based on their expression of Schwann cellspeci®c markers. Compared to embryo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 49 publications
0
11
0
Order By: Relevance
“…We have also presented strong evidence that ErbB-mediated activation of downstream mitogenic signaling pathways is important for schwannoma development. In vitro, expression of a constitutively activated form of ErbB2 in rat SC promotes transformation (Sherman et al, 1999). In vivo, chemically induced activating mutations of ErbB2 trigger malignant schwannoma development in rodents (Nikitin et al, 1991;Buzard et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…We have also presented strong evidence that ErbB-mediated activation of downstream mitogenic signaling pathways is important for schwannoma development. In vitro, expression of a constitutively activated form of ErbB2 in rat SC promotes transformation (Sherman et al, 1999). In vivo, chemically induced activating mutations of ErbB2 trigger malignant schwannoma development in rodents (Nikitin et al, 1991;Buzard et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Anyhow, early biallelic loss of Nf2 function in neural crest-derived cells of the P0Cre;Nf2 flox2/flox2 ;p53 þ /À mice shifts the tumour spectrum from osteogenic to peripheral nerve sheath tumours. Although it has been demonstrated that the developmental stage of Schwann cells may determine their susceptibility to tumour-initiating alterations (Jin et al, 1993;Sherman et al, 1999), a concomitant modification of the tumour spectrum has not been described yet.…”
Section: Also P0crementioning
confidence: 99%
“…2). Immortalization with neu has been reported (Frederiksen et al, 1988;Sherman et al, 1999), but rare.…”
Section: Immortalizing Genesmentioning
confidence: 99%